Negotiating Identity and Language in Child-Naming: Parental Perspectives in Minangkabau–Japanese Intercultural Marriages - Lestari, Imelda Indah; Putri, Darni Enzimar; Rumbardi, Rumbardi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Andalas, 2025)
This study explores the practice of naming children in Minangkabau–Japanese intercultural families from linguistic and socio-cultural perspectives. A child’s name reflects identity, cultural values, and the ethnic affiliations of parents from two distinct cultural backgrounds. Based on qualitative data from questionnaires, this research reveals naming strategies and the dynamics of identity negotiation involved in the process. The contrasting cultural contexts—Minangkabau as the world’s largest matrilineal society, and Japan with its traditional patrilineal